Thermodynamics of equilibrium and partitionless solidifications in glass forming binary eutectic alloys. (April 2016) - Zhao, Linran; Li, Zijing; Gao, Yanqin; Bo, Hong; Liu, Yingdan; Wang, Li-Min
Abstract: T 0 curves in the phase diagrams have been proven useful to understand thermodynamically glass formation in metallic alloys, emphasizing the importance of the metastable solid solutions crystallized partitionlessly. Here we focus on four typical binary eutectic alloys with distinct glass-forming abilities and interatomic interactions, Ag60 Cu40, Sb17.5 Pb82.5, Au81.4 Si18.6, and Ni24 Zr76 . The thermodynamics involved in the liquid–solid solution transition at T 0 temperatures for the alloys of eutectic compositions are quantified, and the validity of the thermodynamic properties is evaluated. The comparison of the melting entropies for the equilibrium and partitionless solidifications reveals a basic relation. Based on the thermodynamics of the equilibrium phases and the solid solutions, an understanding of the glass formation of metallic alloys is proposed. Highlights: The connection of glass forming range with T0 curves has been reviewed. The thermodynamics of the partitionless solidified solid solutions of four eutectic alloys have been studied. A thermodynamic reasoning of the glass forming ability is proposed.